PROBLEMS OF DIGITAL TRANSFORMATION OF UKRAINIAN CORPORATE MEDIA - Oleksandr Lytvynenko (Інтегровані комунікації)
Ukraine is on the path of intensive development of information technologies and digitization in all spheres of society. The impact of the COVID-19 pandemic and the war in Ukraine further accelerated the digital transformation process of all industries, especially the media. The development of digital technologies is significantly changing the ways of production, distribution and consumption of media content in the conditions of the modern market environment. Ukrainian corporate media must adapt to these changes to remain competitive and effective. These processes open up new opportunities for corporations in marketing, communications and customer engagement. Successful digitization of corporate media should be based on providing access to relevant information resources, increasing employee interaction and reducing communication barriers. One of the main problems of introducing digital technologies in corporate media is the lack of a clear vision of the goals on the part of the participants in the process and the coordination of the plan of activities. A comprehensive analysis of successful cases and the development of a generalized strategy for implementing digital technologies allows for formulating a theoretical basis for the digital transformation of corporate media, which requires considerable effort and is a strategic choice for modern business. In most cases, this process involves restructuring business operations and rethinking how to work with customers according to time requirements and the constantly changing market situation. The main goal is to outline the ways of adapting Ukrainian corporate media to the digital era and analyze the challenges that arise in connection with the development of new technologies, developing a recommendation on the effective digitalization of corporate media that will contribute to the improvement of communication strategies and the image of the corporation.